3D Printed and Photonically Cured Graphene UHF RFID Tags on Textile, Wood, and Cardboard Substrates. (20th June 2017) - Akbari, M.; He, H.; Juuti, J.; Tentzeris, M. M.; Virkki, J.; Ukkonen, L.
Abstract : This paper introduces 3D direct writing and microdispensing of graphene ultrahigh frequency (UHF) radio-frequency-identification (RFID) antennas on textile, wood, and cardboard substrates, subsequently cured either by conventional oven or photonically by pulsed Xenon flashes. Photonic-cured passive UHF RFID graphene tags on cardboard, wood, and textile substrates achieve read ranges of 5.4, 4.6, and 4 meters, respectively. These results are superior to those achieved by the oven-cured tags that featured read ranges of 4.8, 4.5, and 3.6 meters, respectively. This work presents the first integration of 3D printing and photonic curing of graphene antennas on low-cost versatile substrates.